2022
DOI: 10.1002/agj2.20952
|View full text |Cite
|
Sign up to set email alerts
|

Distant somatic hybridization alters the structure of wheat root bacterial microbiota

Abstract: Root microbiota affect the host plant's adaptation to adverse environments. The structure and function of plant root bacterial communities are affected by soil physicochemical properties and plant genotypes. Distant hybridization is a common breeding strategy to introgress the excellent genes of wild relatives into the crop genome. The effect of distant hybridization on the crop root microbiota has not been reported. In this study, the structure and function of root bacterial community of the somatic hybrid wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 64 publications
0
1
0
Order By: Relevance
“…It was reported that symmetric somatic hybridization induced a whole-genome scale shift of synonymous codon usage bias (SCUB) via whole genomic shock rather than local chromosomal shock. And there is a complicated association between genetic and epigenetic variation like DNA methylation [82].The process of distant somatic hybridization was recently reported to alter key regulating genes and altered the structure and function of the root bacterial community in somatic hybrid wheat introgression lines SR3 and SR4 [83]. Hence, asymmetric somatic hybridization could be an efficient strategy for wheat breeding.…”
Section: Somatic Hybridization In Department Of Cereal Crops Of Grami...mentioning
confidence: 99%
“…It was reported that symmetric somatic hybridization induced a whole-genome scale shift of synonymous codon usage bias (SCUB) via whole genomic shock rather than local chromosomal shock. And there is a complicated association between genetic and epigenetic variation like DNA methylation [82].The process of distant somatic hybridization was recently reported to alter key regulating genes and altered the structure and function of the root bacterial community in somatic hybrid wheat introgression lines SR3 and SR4 [83]. Hence, asymmetric somatic hybridization could be an efficient strategy for wheat breeding.…”
Section: Somatic Hybridization In Department Of Cereal Crops Of Grami...mentioning
confidence: 99%
“…Microorganism application in agriculture is an environmentally friendly agricultural practice that can foster sustainable production (Popescu & Popescu, 2022). Yang, Chen, et al (2022) studied the effect of distant somatic hybridization on wheat root microbiota and reported that it may alter the structure of wheat root bacterial microbiota, concluded that root microbiome is an essential community for plant growth and development. Another paper related to the root bacterial community showed that microbial taxa could be integrated into the management strategy of wheat stripe rust .…”
Section: Use and Roles Of Microorganisms In Agricultural Productionmentioning
confidence: 99%